Change Management in The Digital Transformation Era: Challenges and Solutions for Organizations - Hari Supriadi; Olyvia Rosalia (PT. Anagata Sembagi Education, 2025)
This study aims to explore the challenges and solutions in change management faced by organizations during the digital transformation process. In an era marked by rapid technological advancements, organizations must adapt to digital changes to remain competitive and relevant. However, this process is not always smooth, as many organizations encounter challenges such as resistance to change, digital skills gaps, and difficulties in balancing technology adoption with existing organizational culture. This research adopts a qualitative approach using in-depth interviews and case studies to analyze how organizations confront these challenges and the solutions they implement to overcome them. The findings indicate that strong leadership, effective digital skills training, and clear communication are key factors in the success of change management. This study emphasizes the importance of integrating digital transformation with an organizational culture that supports innovation and collaboration.